Roleplay Based English Language Learning Strategies and Interactive Programs to Improve the Speaking Skills and Interest of Elementary School Students in Rural Areas in Indonesia - Systematic Literature Review - Tania, Mira (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze the effectiveness of roleplay-based English learning strategies and interactive programs in improving the speaking skills and interest of elementary school students in rural areas in Indonesia. Through a systematic literature review, various community service activities conducted by the team from the Nursing Study Program at STIKes Mitra Husada Medan have shown positive responses from various parties, including religious leaders, community leaders, and local government. These activities combine theory (60%) and direct practice (40%), where the roleplay method has proven effective in improving the English-speaking skills of children aged 10-13 in Bangun Sari Village, Silau Laut District. The findings of this study emphasize the importance of early English language learning in the era of globalization. Interactive, media-based, and game-based methods have been proven to increase students’ interest, motivation, and speaking skills. These innovations are expected to address challenges such as limited resources and learning support in rural areas, reducing the quality gap in language education between urban and rural regions. Thus, children in villages will have greater opportunities to compete globally.